Facile one-pot solvothermal preparation of two-dimensional Ni-based metal–organic framework microsheets as a high-performance supercapacitor material. Issue 14 (22nd February 2021) - Li, Zhaohua; Sun, Yuan; Hu, Rui; Ye, Shuai; Song, Jun; Liu, Liwei; Qu, Junle
Abstract : Two-dimensional Ni-based metal–organic framework microsheets (Ni-MOFms) were synthesized via a facial one-pot solvothermal approach and exhibited good specific capacities and excellent long-term stability when used for a supercapacitor electrode. Abstract : We report a facile one-pot solvothermal way to prepare two-dimensional Ni-based metal–organic framework microsheets (Ni-MOFms) using only Ni precursor and ligand without any surfactant. The Ni-MOFms exhibit good specific capacities (91.4 and 60.0 C g −1 at 2 and 10 A g −1, respectively) and long-term stability in 5000 cycles when used for a supercapacitor electrode.